Cubipod Manual 2016 - Medina Folgado, Josep Ramon; Gómez Martín, Mª Esther (Universitat Politècnica de València Editorial, 2022)
Cubipod¿ Manual 2016 provides basic criteria for the preliminary design of mound breakwaters protected with single- or double-layer Cubipod¿ armors. Economic, logistic and environmental factors are analyzed to guide the designers in the preliminary design phase of a breakwater.The economic cost of a large mound breakwater usually depends on the geometry of the concrete unit used for the armor layer. Each geometry (cube, Cubipod¿, Tetrapod, etc.) and placement pattern (random, specific, ordered, etc.) can be used for single-layer armoring, double-layer armoring or both.Each armor design alternative, with a different packing density, has a different hydraulic performance and logistic constraints. Although some general rules and comments are applicable to other armor units,Cubipod¿ Manual 2016 is focused on the use of Cubipod¿ units in conventional mound breakwaters.